Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1364/oe.15.002622
|View full text |Cite
|
Sign up to set email alerts
|

The design and simulated performance of a coated nano-particle laser

Abstract: The optical properties of a concentric nanometer-sized spherical shell comprised of an (active) 3-level gain medium core and a surrounding plasmonic metal shell are investigated. Current research in optical metamaterials has demonstrated that including lossless plasmonic materials to achieve a negative permittivity in a nano-sized coated spherical particle can lead to novel optical properties such as resonant scattering as well as transparency or invisibility. However, in practice, plasmonic materials have hig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
247
3
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 216 publications
(259 citation statements)
references
References 36 publications
8
247
3
1
Order By: Relevance
“…These resonances were exploited in [6] and [7], where efficient MTM-based ESAs were proposed, and in [8] where MTM-inspired electrically small near-field parasitic resonators were used as impedance transformers to realize matching of the overall antenna system to its source and to the wave impedance of the medium in which it radiates. While the above works focused on radio and microwave frequencies, similar highly resonant properties, for potential use in nano-sensing, -amplifying and -antenna applications, were reported for passive plasmonic-based configurations at optical frequencies, see e.g., [9], [10] and the works referenced therein, as well as active plasmonic-based configurations, see e.g., [11] and the works referenced therein, as well as [12] and [13]. In particular, interesting enhancements of directivity patterns for higher order mode sub-wavelength radiators made of DPS materials in conjunction with passive MTMs or plasmonic materials, were reported in [10], this providing an alternate route towards sub-wavelength radiators with high directivities.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…These resonances were exploited in [6] and [7], where efficient MTM-based ESAs were proposed, and in [8] where MTM-inspired electrically small near-field parasitic resonators were used as impedance transformers to realize matching of the overall antenna system to its source and to the wave impedance of the medium in which it radiates. While the above works focused on radio and microwave frequencies, similar highly resonant properties, for potential use in nano-sensing, -amplifying and -antenna applications, were reported for passive plasmonic-based configurations at optical frequencies, see e.g., [9], [10] and the works referenced therein, as well as active plasmonic-based configurations, see e.g., [11] and the works referenced therein, as well as [12] and [13]. In particular, interesting enhancements of directivity patterns for higher order mode sub-wavelength radiators made of DPS materials in conjunction with passive MTMs or plasmonic materials, were reported in [10], this providing an alternate route towards sub-wavelength radiators with high directivities.…”
Section: Introductionmentioning
confidence: 86%
“…Previous results [11]- [14] have demonstrated that highly resonant sub-wavelength CNPs can be designed by including gain, e.g., inside their nano-cores. Such active configurations were found to lead to scattering crosssections that are orders of magnitude larger than the values predicted by their geometrical sizes, see e.g., [11] and the works referenced therein, as well as to the enormous radiated powers for localized excitation sources [12]- [14].…”
Section: Background -Sub-wavelength Resonances In Cnpsmentioning
confidence: 99%
See 3 more Smart Citations